Pelatihan Komunikasi Pelayanan Kesehatan kepada Petugas Kesehatan di Puskesmas Cempaka Putih - Caninsti, Riselligia; Febriani, Zulfa; Brebahama, Alabanyo (University of Merdeka Malang, 2020)
Health service communication is a form of communication that occurs between health service providers (such as doctors, nurses, midwives, pharmacists, and other health workers) with patients, patients' families or with other health workers. In essence, health service communication is a process of interaction between two parties to obtain information, provide information and provide support, which is carried out in a health setting. Effective communication can reduce patient doubts about the treatment process and increase patient compliance with a series of treatments, so that health problems can be resolved. Therefore, health workers need to maintain a good cooperative relationship with patients. Based on the community service activities that have been carried out, data are obtained that health service communication training provided to health workers at the Cempaka Putih Health Center shows the results of an increase in understanding and knowledge of training participants regarding techniques for communicating health services to patients. The future program is expected to not only sharpen the knowledge and understanding possessed by participants, but can also be improved by training the operational technical skills of health practitioner participants in communicating health services.Â How to cite:Caninsti, R., Febriani, Z., Brebahama, A. (2020). Pelatihan Komunikasi Pelayanan Kesehatan kepada Petugas Kesehatan di Puskesmas Cempaka Putih. Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 5(1), 47-52.DOI: https://doi.org/10.26905/abdimas.v5i1.3299